2021
DOI: 10.1002/er.6752
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of holmium oxide on germanium‐based metal‐oxide‐semiconductor capacitor

Abstract: The influence of different thermal oxidation/nitridation durations (5,10,15, and 20 minutes) at 400 C for transforming metallic Ho sputtered on Ge substrate in N 2 O gas ambient have been systemically investigated to develop Ho 2 O 3 /Ge based on metal-oxide-semiconductor (MOS) device. The structural and chemical properties of the film were characterized using X-ray diffraction spectroscopy, X-ray photoelectron spectroscopy (XPS), and high-resolution transmission electron microscopy. Cubic-Ho 2 O 3 dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
(255 reference statements)
1
2
0
Order By: Relevance
“…Figure 1(a) depicts the GIXRD pattern for Ho 2 O 3 thin film. It is clear from the figure that the major diffraction peaks of Ho 2 O 3 film are at 2θ = 28.85°(222), 33.59°(400), and 48.24°(440) respectively, which are consistent with the reported 2θ values of Ho 2 O 3 [28][29][30]. In addition to Ho 2 O 3 peaks, we do observe peaks pertinent to FTO at 2θ = 26.38°(110), 37.59°(200), 51.38°(211), 54.47°(220), 61.43°(310), 65.39°(301), 78.23°(321) respectively [31].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 1(a) depicts the GIXRD pattern for Ho 2 O 3 thin film. It is clear from the figure that the major diffraction peaks of Ho 2 O 3 film are at 2θ = 28.85°(222), 33.59°(400), and 48.24°(440) respectively, which are consistent with the reported 2θ values of Ho 2 O 3 [28][29][30]. In addition to Ho 2 O 3 peaks, we do observe peaks pertinent to FTO at 2θ = 26.38°(110), 37.59°(200), 51.38°(211), 54.47°(220), 61.43°(310), 65.39°(301), 78.23°(321) respectively [31].…”
Section: Resultssupporting
confidence: 85%
“…Paivasaari et al [26] have demonstrated the electrical characteristics and physical properties of Ho 2 O 3 thin film grown onto silicon (100) substrate. Tung et al have reported Ho 2 O 3 films with high-dielectric constant for PH sensing applications [27,28]. Ho 2 O 3 consists distinct properties apart from its paramagnetic nature, which may be useful for various technological applications.…”
Section: Introductionmentioning
confidence: 99%
“…By further enhancing the wet oxidation temperature to 1000 C, a reduction in at% of nitrogen (2.25 at%) in the Ga x Ce y O z thin film could be possibly related to the aggressiveness of the wet oxidation process, wherein the inward diffusing of oxygen and/or OH À ions have gained sufficient energy to shatter the nitrogen diffusion barrier layer and thus, the nitrogen ions would diffuse away from the Ga x Ce y O z thin film. The variation in the elemental composition of the Ga x Ce y O z thin films wet oxidised at 400 C, 600 C, 800 C, and 1000 C would influence the generation of microstrain (ε) as well as the growth of crystallize size (D) of the investigated films, which could be calculated based on Williamson-Hall (W-H) approach, as expressed via the following Equation 38,39 :…”
Section: Resultsmentioning
confidence: 99%